(3TQM GdePgH GdMb aj YdI bhGe GdCQVs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdaUd GdChd ai HjGf eGgi GdLgGJ GdaUd GdKGfi ai Cf GdLgGJ dGjJUhQ s
(3BNQgG (B:s
(3hbGd HYVge Ef CLRGA GdCQV CfeG JJMQc Edi GdCQV YFbkG agPG eG MVQfG ai gPg GdSGYI ef BQGA GdbOeGA ai GdCQV hdfNJe GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKI YTQs
(3WdH gPG GdTQM GdTjN CHG GdMSjf CMeO Hf eMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs